Предмет:
Другие предметыАвтор:
анонимy = (x3 + x2 + 16) / x;
Производную будем искать по формуле:
(u / v)\' = (u\' * v - v\' * u) / v2;
Находим производную функции:
y\' = ((x3 + x2 + 16) / x)\' = ((x3 + x2 + 16)\' * x - x\' * (x3 + x2 + 16)) / x2 = ((3x2 + 2x) * x - (x3 + x2 + 16)) / x2 = (3x3 + 2x2 - x3 - x2 - 16) / x2 = (2x3 + x2 - 16) / x2 = 2x + 1 - 16 / x2;
Ответ: y\' = 2x + 1 - 16 / x2.
Автор:
potter3Добавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть